Efeito do extrato do rizoma de Curcuma longa e solução de curcumina em Alternaria solani e controle de pinta preta em tomateiro - Balbi-Peña, Maria Isabel (2005)
Early blight, caused by Alternaria solani, is one of the most important diseases of tomato in Brazil. This disease affects leaves, stems, petioles and fruits causing important economicaI losses. New alternatives to fungicides have been evaluated to control the diseases with low environmental impact and low toxicity to living beings. The discovery of vegetal secondary compounds with antimicrobiotic activity or secondary compounds that induce disease resistance shows to be very promissory. Turmeric, Curcuma longa, has compounds in its rhizomes with proved antimicrobiotic activity. The objectives of this study were to evaluate the in vitro fungitoxic activity of turmeric extracts and curcumin against A. solani and to determinate their potential in the control of tomato early blight. Four different concentrations (1, 5, 10 and 20%) of aqueous extracts of turmeric rhizomes (sterilized by autoclavation) and four curcumin solutions (50, 100, 200 and 400 mg L-1) were incorporated into potato dextrose agar medium in order to evaluate fungal micelial growth and esporulation. To evaluate the effect of autoclavation, 10% and 15% turmeric extracts were sterilized by filtration. The effects of autoclavated and non autoclavated turmeric extracts and curcumin on in vitro spore germination were tested. The concentrations of 10 and 15% non autoclavated turmeric extracts inhibited the micelial growth by 38,2% and 23,2%, respectively, and the fungal sporulation by 71,7% and 87% respectively. When the turmeric extracts were autoclavated, neither micelial growth nor spore germination was inhibited and the effect on the sporulation was reduced, suggesting the presence of thermolabile antimicrobiotic compounds. The non autoclavated 5% extract inhibited by 15% the spore germination. At the highest concentration, the curcumin solution inhibited the micelial growth by 29,5%. Neither in vitro esporulation nor spore germination was affected by curcumin. At a greenhouse experiment, desease severity, fruit production and classification were evaluated. The treatments were: 1 and 10% turmeric extracts, 50 e 100 mg L-1 curcumin solutions, acibenzolar-S-metil (ASM) (2,5 g 100 L-1 of a.i.), copper oxychloride (110 g L-1 of a.i.), azoxystrobin (40 g L-1 of a.i.) and control (water). The disease control showed by turmeric extracts and curcumin solutions was similar to cuprous fungicide, but inferior to azoxystrobin control. There was no statistical difference in comercial fruit production between treatments. Only 50 mg L-1 curcumin treatment had higher porcentage of bigger fruits compared to the control. Another experiment with tomato plants growing in vases was performed with the subject of veryfing resistance induction. After 26 days of transplanting, the 7th. leaf was sprayed with turmeric extract (1 and 10%), curcumin (50 e 100 mg L-1), ASM (2,5 g a.i. 100 L-1) and water. Seventy two hours later, 7th. treated leaf and 8th. untreated leaf were inoculated with A. solani. At 7th. leaf, 10% turmeric extract and 100 mg L-1 curcumin treatments showed an statistically inferior area under disease progress curve, compared to the control, what could suggest induction of local resistance or direct antimicrobiotic activity. At 8th. leaf, only 10% turmeric extract shows significant difference compared with the control, what could mean a systemic resistance induced by turmeric extract. These results show the potential of turmeric and curcumin in the control in tomato early blight.